The complete chloroplast genome sequence of Kandelia obovata (Rhizophoraceae) - Chen, De-Qiang (Mitochondrial DNA B Resour, 2019)
The complete plastid genomic data will be helpful to study the origin, evolution and the relationship between the phenotype and environment of Kandelia obovata. In this study, we determined the complete chloroplast genome sequence for K. obovata using Illumina sequencing data. The complete chloroplast sequence is 168,046 bp, including large single-copy (LSC) region of 94,755 bp, small single-copy (SSC) region of 19,953 bp, a pair of invert repeats (IR) regions of 26,669 bp. Plastid genome contains 119 genes, 79 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis base on 13 plastid genomes indicates that K. obovata is sister to Rhizophora stylosa, which forms a base clade of Myrtales in Rhizophoraceae.